Search for secondary osteoporosis: are Z scores useful predictors?. Issue 999 (24th February 2009) - Swaminathan, K; Flynn, R; Garton, M; Paterson, C; Leese, G
Abstract : Aim: To determine whether Z scores can be used to predict the likelihood of patients having a secondary cause of low bone mineral density. Methods: A retrospective cross sectional study was conducted among 136 consecutive patients with osteoporosis at Ninewells Hospital, Dundee, UK, between 1998–2002. Results: 20.5% of female patients in this study were identified with previously unrecognised contributors to the low bone mineral density. In women, at a Z score cut-off of −1, the sensitivity of detecting a secondary cause for osteoporosis is 87.5% with a positive predictive value of 29.2%. Conclusion: In women, a Z score of −1 would identify a majority of patients with a secondary cause for low bone mineral density and identifies patients who would especially benefit from a thorough history and clinical examination.